Environmental determinants of habitat and kill site selection in a large carnivore: scale matters - Davidson, Z; Valeix, M; Loveridge, A; Hunt, J; Johnson, P; Madzikanda, H; Macdonald, D (2012)
Scale influences habitat selection. We used data from 30 global positioning system radiocollared lions (Panthera leo) collected between 2003 and 2007 in Hwange National Park, Zimbabwe, and information from 227 locations where lions had made kills, to assess how lions select habitat at 3rd-order habitat selection (selection of habitats within home ranges) and 4th-order habitat selection (selection of kill sites within the habitats used). Within home range, lions preferentially selected bushed grasslands and sites close to water holes, which are both characterized by high prey abundance. However, lions preferentially killed in thickets, where prey abundance was not the highest but where prey catchability may be higher because of dense vegetation. Our results support the suggestion that there are different determinants of habitat selection at different scales with prey abundance being the main driver of habitat selection at 3rd-order and prey catchability the main driver at 4rth-order habitat selection. © 2012 American Society of Mammalogists.